MINIMUM VIABLE CYBERSECURITY FRAMEWORK FOR PROTECTING CYBER ATTACKS FROM EXTERNAL THREAT VECTORS - Arunachalam, Chidhanandham (Digital Repository of Theses, 2023)
In cybersecurity, an attack surface refers to the potential vulnerabilities and entry points that an attacker could use to compromise a system, network, or application. Thus, understanding and managing the attack surface is a critical component of effective cybersecurity, as it helps to reduce the risk of successful attacks and protect sensitive data and systems from unauthorized access or damage. Through this research, my main objective was to create a minimum viable cybersecurity framework for protecting cyber-attacks from external threat vector that helps in preventing and remediating the most common cyberattack threat vectors across industries, platforms, and threat landscapes with minimal effort. I used Alexa’s Top 1000 websites and 200 random websites as a source input and performed passive scans on those websites using the Threat Meter tool (An External Attack Surface Monitoring Tool built by Sumeru Software Solutions). From the scans, I obtained raw data containing classes such as Industry, Attack Vectors, Threat Vectors, Threat score, Total no of Threats, and Fail Ratio. To achieve the main objective, I first performed an initial data analysis on the raw data obtained from the scans and arrived at inferences based on the initial analysis. I then used the inferences to answer some questions which helped me to build the framework. Wherever initial analysis inference was inadequate, I performed data sampling over the raw data to arrive at new inferences. My goal was to build a security framework that would help in preventing and remediating the most common cyberattack threat vectors across industries, platforms, and threat landscapes with minimal effort.